ANALISIS PENERAPAN PEMASARAN HIJAU DALAM STRATEGI PEMASARAN - Bobik, Feronaudy Kevin De (Smart Education, 2025)
Abstract: This study aims to determine the right marketing strategy to be applied to the Drop Coffee branch of the business that uses the Green Marketing concept. The type of research used is qualitative research. The research method applied to the research is SWOT analysis. The problem in this research is